METHOD OF CONVERSATION IN PSYCHODIAGNOSTICS BY PROJEC- TIVE METHODS IN WORKING WITH STUDENTS OF NAUTICAL SPECIALTIES - Шевченко, Росіна Павлівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
The article reflects the features of the use of introspection as an auxiliary method of psychodiagnostics of students in nautical specialties using the "Non-existent animal" methodology. The possibilities of introspection were studied as the subject is focused on his own thoughts and experiences; messages by the individual in the form of original reports of their own experiences; in the form of thinking aloud about circumstances that need to be discussed with a specialist.To study the peculiarities of the psychoemotional state after long voyages, a group of 50 people was recruited from among 4th year students of Odessa National Maritime University who completed training in the specialty curriculum and who spent at least 3 months at sea. The study was conducted with the information consent of the surveyed, in compliance with the norms of ethics and bioethics. Analysis of the data suggests a range of psychoemotional features of students from a dedicated research group: the presence in 56% of the studied tendencies to feel self-doubt, low self-esteem, depression, indecision, demonstration in the social model of disinterest in their position, recognition from others; 28% of the total number of studied students of nautical specialties showed the presence in the structure of the nature of the elements of egocentricity, the desire to take care of themselves primarily, neglecting the interests of other people in some cases, 16% of the students studied had a tendency to reflect, a subject’s need to understand the situation in life , reflections on one’s own place, importance in the eyes of others, one’s own utility, 78% of those who took part in the study found a tendency of interest in information about themselves, and seek out the need for approving reactions from the interlocutor, in some cases perceive evaluative judgments of others as a channel of emotional communication, 28% of the total number of surveyed students in the nautical professions do not need active verbal communication. 52% of the total number of students studied showed a tendency for increased anxiety. 74% of those surveyed showed a trend of “self-propagation”, curiosity, a desire to participate in more vital projects, a desire to declare oneself, to win one’s place in society.